Electron Backscatter Diffraction Analysis of Low-Misorientation-Angle Boundary and High-Energy Boundary in the Hot-Rolled Plate of Grain-Orientated Silicon Steel - Xiang Zou; Qingyou Liu; Shengtao Qiu (Metals)
In order to study the texture evolution and the formation of an inhomogeneous microstructure in hot-rolled plate of grain-orientated silicon steel, Fe3C (hexagonal) and ferrite phases in the subsurface layer were studied using electron backscatter diffraction. The results indicate that fiber texture (ferrite) mainly composed of {441}<104> and (110)[001] Goss oriented grains was formed at a depth of 25% of the thickness of hot-rolled plate. Matrix grains in the subsurface layer were arbitrary separated into irregular large grains (≥40 μm) and fine grains (<40 μm), and the grain boundary characteristics and texture evolution of matrix grains were studied. The results indicated that the formation of the colonies of fine grains was the result of dynamic recrystallization, and high-frequency low-misorientation-angle boundaries (0~20°) were formed between large grains (≥40 μm) and fine grains (<40 μm), which can be considered as the irregularity of large grains caused by solid-state wetting. Due to the texture evolution of large grains (≥40 μm), a large number of high-energy boundaries (20~45°) were formed between irregular large grains (≥40 μm), resulting in rapid consumption between adjacent large grains and the elongation of large grains along the rolling direction. Therefore, it can be assumed that the migration of low-misorientation-angle boundaries (0~20°) under solid-state wetting and high-energy boundaries (20~45°) are important mechanisms for non-uniform grain growth in hot-rolled plate of grain-orientated silicon steel.